Academic Senate Minutes 2004-12-02 - Academic Senate:::::::::
Chair's Report. Agenda amended and approved. Minutes of 11/11/04 approved. Copeland Creed Advisory Committee recommendations approved. Endowed Chairs Policy approved. Withdrawal Policy approved. Cheating and Plagiarism Policy revision first reading. Resolution in Support of Boycotting Holt, Rinehart and Winston and Glencoe/McGraw-Hill Publishers first reading. Motion: That administration carry out existing course repeat policy, i.e. the policy adopted by the Academic Senate. Most recent grade and no deadline - Approved. Motion to refer to Executive Committee the issue of changing Senate approved policy without going through appropriate procedures – Approved. Associated Students report. Statewide Senator report. APC report